Total knee arthroplasty: implant selection and surgical considerations. Issue 1 (February 2021) - Porteous, Andrew; Curtis, Alexander
Abstract: Choosing a total knee arthroplasty implant can be confusing, with implant manufacturers all providing a wide range of implants even within the same brand. These may vary by design philosophy, fixation, constraint, materials and construct. A surgeon will need to have considered the evidence before making a choice of implant, and this evidence can be in the form of large cohorts of registry-based data, that may lack detail, or small studies that may be too small to be valid or have wider application. This article reviews the sources of data available to surgeons and discusses the categories of implant available to the surgeon. Variations in patient anatomy and pathology may require a surgeon to be familiar with a range of implant options. Surgeons should be aware of how their chosen implant performs, not just in studies from the designer, but in independent series and on national registries, and should know the UK Orthopaedic Data Evaluation Panel (ODEP) rating of the specific detailed construct that they are regularly using.